2022
DOI: 10.3390/agronomy12051021
|View full text |Cite
|
Sign up to set email alerts
|

Rerouting Artificial Light for Efficient Crops Production: A Review of Lighting Strategy in PFALs

Abstract: A plant factory with artificial light (PFAL) is defined as an advanced agricultural production system with a precisely controlled environment, playing an important role in vertical farming and urban food supply. Artificial light is one of the core technologies in PFALs and accounts for a large part of energy consumption; elevating the light utilization efficiency of plants is vital for the sustainable development of PFALs. Meanwhile, the enclosed structure of the plant factory resulted in the independence of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 78 publications
0
4
0
1
Order By: Relevance
“…Light can be naturally emitted by the sun, undergo spectrum transformation, or even be redirected. The primary energy source for traditional crop cultivation is sunlight, and the light that plants intercept in a natural setting fluctuates and is complex 14 . During cloudy days and especially in winters plants receive much less light than that required for its normal growth and development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Light can be naturally emitted by the sun, undergo spectrum transformation, or even be redirected. The primary energy source for traditional crop cultivation is sunlight, and the light that plants intercept in a natural setting fluctuates and is complex 14 . During cloudy days and especially in winters plants receive much less light than that required for its normal growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…continuous lighting also increased dry and fresh shoot biomass and plant growth of lettuce (cv. Yidali) under red and blue LEDs 14 . Similar results were obtained for Nasturtium ( Tropaeolum majus L.) plants 55 .…”
Section: Introductionmentioning
confidence: 99%
“…Light, temperature, humidity, and plant hydroponic nutrition must be controlled and this is an energy-demanding process. Artificial light is one of the core technologies in CEA and accounts for the largest part of the capital and operation costs [4,5]; therefore, technological and biological strategies for energy-efficient plant lighting in CEA have recently been attracting attention. In the last decade, LED fixture costs have decreased and lighting photon efficacies have increased [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The lighting spectrum, photoperiod, and photosynthetic photon flux density (PPFD) can be optimized, maximizing the efficiency with which plants intercept and use light to produce marketable biomass, which has the potential to reduce input costs and increase yields and profitability [4,5,8]. The light amount (daily light integral, DLI) necessary for optimal lettuce productivity in CEA is acknowledged to be about 14-17 mol m −2 per day; in a literature review, a 16 h photoperiod and 250 µmol m −2 s −1 were found to be the average optimum for yield and resource use efficiency in hydroponic lettuce cultivation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…이들 광원 중에서 MH나 IL, HPS는 주로 온실에서 강우, 폭설, 황사 등 자연광이 부족한 시기에 광을 보충해주는 보광광원으로 이용하고 있다. 한편 LEDs는 형광등이나 기타 광원에 비해 수명이 길고 전력소모량이나 광원으로부터의 발 열량이 적어 근접 조사가 가능하므로 다단재배 방식을 채택하 는 인공광 재배시설인 식물공장에서 활용도가 높은 광원이다 [11,20,21].…”
unclassified